21st Century Teaching Strategic Competencies to be Developed by ELT Instructors - Pachon Jaramillo, Alejandro (Coloquio, 2023)
This reflective article dives into the imperative need for ELT instructors to teach21st-century skills. The study investigates various strategies to foster language learningthrough ICTs’ core elements integration within culturally responsive classrooms. Datawere gathered through an extensive bibliographic analysis, encompassing papers, articles,and documents from diverse sources. The resultant findings underscored the vital need toincorporate ICTs and culture-based strategies by ELT instructors to propel students towardsuccess in the dynamic horizon of 21st-century language acquisition.